Towards Evaluating the Historicity of the Claim that Peter the Iberian Descended from the Iberian Royal Family - Cornelia B. Horn (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
In the article that discusses the place, date and the purpose of the creation of the Georgian alphabet, Werner Seibt commented on the difficulties Christianity experienced in Georgia in the fifth century as a context that motivated some Georgians, who were wished to practice their Christian faith freely, to leave Georgia and go abroad. The sources suggest that a good number of them went to the Holy Places in Syria and Palestine, initially as pilgrims. Not infrequently they stayed on for longer as ascetics. Having learned the monastic craft, Georgian-speaking monks established monasteries of their own. Likely the most famous and earliest Georgian pilgrim to the Holy Land among them was Peter the Iberian.